The Melancholic Gaze - Śniedziewski, Piotr (Literary and Cultural Theory, 2018)
This book consists of nine chapters devoted to representations of melancholia in 19th-century art and literature. A noteworthy feature of the book is its use of concepts from later works by Sigmund Freud, Jean Clair, Jean Starobinski, Julia Kristeva and others. Those concepts elucidate further contexts of the notion of melancholia, which are presented not in isolation but juxtaposed with the philosophical background of the concept (starting from Hippocrates and Aristotle). Thus, the book not only provides a survey of images and modes of behaviour of 19th-century individuals, but also discusses the meanings of melancholia as they appeared in European culture over time.